Options for Gas-to-Liquids Technology in Alaska - Robertson, Eric Partridge (Idaho National Laboratory, 1999)
The purposes of this work was to assess the effect of applying new technology to the economics of a proposed natural gas-to-liquids (GTL) plant, to evaluate the potential of a slower-paced, staged deployment of GTL technology, and to evaluate the effect of GTL placement of economics. Five scenarios were economically evaluated and compared: a no-major-gas-sales scenario, a gas-pipeline/LNG scenario, a fast-paced GTL development scenario, a slow-paced GTL development scenario, and a scenario which places the GTL plant in lower Alaska, instead of on the North Slope. Evaluations were completed using an after-tax discounted cash flow analysis. Results indicate that the slow-paced GTL scenario is the only one with a rate of return greater than 10 percent. The slow-paced GTL development would allow cost saving on subsequent expansions. These assumed savings, along with the lowering of the transportation tariff, combine to distinquish this option for marketing the North Slope gas from the other scenarios. Critical variables that need further consideration include the GTL plant cost, the GTL product premium, and operating and maintenance costs.